The effect of initial strength levels on the training response to heavy resistance training and ballistic training on upper body pressing strength - Young, K. P.; Gabbett, T. J.; Haff, G. G.; Newton, R. U.; Watts, D. G.; Sheppard, J. M. (Journal of Australian Strength and Conditioning, 2013)
It has been shown that heavy strength training and ballistic training are effective methods of improving maximal strength. However, the magnitude of improvement realised from strength training differs as a result of initial strength levels. Consequently, strength levels must be taken into consideration when designing training programs. While this concept appears to have important practical implications, there is little information on the impact of initial upper body strength levels and the subsequent training response to heavy resistance training or ballistic training. Thus, the purpose of this study was to examine the effects of initial strength levels on the training response to two different training methodologies.